The Effect Of Affiliation Need On Fear Of Missing Out Among Adolescent Social Media Users: The Mediating Role Of Self-Confidence - Basti, Basti; rahmah, Nur; Kiling, Yohanes Indra (Seminar Nasional LP2M UNM, 2023)
Abstract. Unwise social media uses bring about some risk of fear of missing out (FoMO), especially for the adolescents who have been addicted to social media. This research aims to examine the effect of affiliation need on FoMO among adolescent social media users, with self-confidence as a mediator. The research used a quantitative survey. The participants consisted of 385 adolescent social media users aged 15-18, domiciled in Makassar City, selected by using an accidental sampling technique. Data collection was performed by using International Orientation Scale (IOS), The Test of Self Confidence, and Fear of Missing Out Scale. Data analysis technique used a path analysis with an aid of version 8.80 Lisrel and version online Sobel. The findings revealed that self-confidence mediates partially the effect of affiliation need on FoMO among adolescent social media users (t = 2.14 > 1.96). Adolescent social media users should fulfill their affiliation needs as necessary and directly and build strong self-confidence so as to prevent FoMO problems. Kata Kunci: FoMO; affiliation need; self-confidence; adolescent social media users